Review of Arthur M. Jacobs, Neurocomputational Poetics. How the Brain Processes Verbal Art (Anthem Press, 2023) (ENTHYMEMA, 2024)
Review of Arthur M. Jacobs, Neurocomputational Poetics. How the Brain Processes Verbal Art. Anthem Press, 2023.